A dramatic existence: Undergraduate preparations for a creative life in the performance industries. Issue 4 (August 2020) - Higdon, Rachel Delta; Chapman, Kate
This article focuses specifically on drama and theatre higher education (HE) programmes and preparation for potential graduate work. The article investigates working in the creative industries and in the performing arts (particularly within acting) and how HE students in the United Kingdom prepare for this life. The growth of the creative industries and successful applied drama in the public and private sectors has also brought business interest in how drama and theatre processes can benefit other workplaces, outside of the creative arts. The article addresses current policy, initiatives and partnerships to broaden inclusion and access to creative work. The research explores drama undergraduate degrees and the university's role in supporting a successful transition from HE to graduate work. Students perceive the university world as safe and the graduate world as precarious and unsafe. The research findings have resonance with other undergraduate degrees, outside of the arts and the role the university plays in student transitions from the university to the graduate environment.